TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP STATUS CERAI TALAK DI LUAR PENGADILAN AGAMA (Pandangan Ketua Pengadilan Agama Bondowoso) - Muhammad Jufri; A. Muhyiddin Khotib (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
Divorce is the final path that must be taken in resolving domestic disputes and troubles, where the fracture of the household is no longer possible to restore, even if allowed to drag on, it is feared that it will cause the split of the families of both parties. The results of the review of Islamic law and positive law on the status of divorce talak that were passed outside the Bondowoso Religious Court, that the status of divorce talak outside the Religious Court in terms of Islamic legal aspects is not valid, even though it wins in classical jurisprudence, because talak is the absolute right of a husband. This kind of situation is viewed from the point of view of maintaining family interests, legal certainty and public order which does not create maslahat, even harms much, especially for women. Meanwhile, the view of the Head of the Bondowoso Religious Court on the legal status of divorce divorcees who were sentenced outside the Religious court is seen from the aspects of Islamic law and positive law is invalid, because it does not have legality issued by a religious court.